(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
This essay aims to investigate the economic dimension of the late medieval Lombard lordship. At first, the survey proposes a classification of thirteen- and fourteenth-century lordships, then turns its attention to two case studies: the lordship of the cadet branches of the Visconti family, and that of the Borromeo family, chosen due to their specific relevance, the availability of sources, and their morphological diversity. The former became the owners of around fifteen castles in the countryside of Milan since the end of the thirteenth century. The latter, thanks to the ducal support, were able to constitute a great feudal dominion near the Lake Maggiore around 1450. The analysis focuses on the most important lords’ assets; the ways in which gentlemen managed goods and rights; the overall profitability of lordships.